2022
DOI: 10.1108/omj-04-2021-1232
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study on the impact of learning theory on gamification-based training programs

Abstract: Purpose This study aims to investigate gamification-based training program through the lens of self-determination theory and in the context of corporate training programs. It integrates the self-determination theory, game elements and learning outcomes in gamified training programs to derive insights. Design/methodology/approach Data is sourced from software development companies operating in the city of Bangalore in India. It applies the partial least square structural equation modeling to investigate the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…As mentioned, the findings recognized in the case example support notions from SDT (Kulkarni et al , 2022) in that multiple simulations can help student learners’ sense of autonomy, competence and their ability to relate to the program, as well as elements from BRT (Tani et al , 2021) such as values, global motives and intention that can be connected to the multisimulation efforts. Overall, using multiple simulations for experiential learning in management education courses can provide a number of benefits that help students better understand and apply the concepts they are learning, while also developing valuable workplace skills such as problem-solving, communications and teamwork.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…As mentioned, the findings recognized in the case example support notions from SDT (Kulkarni et al , 2022) in that multiple simulations can help student learners’ sense of autonomy, competence and their ability to relate to the program, as well as elements from BRT (Tani et al , 2021) such as values, global motives and intention that can be connected to the multisimulation efforts. Overall, using multiple simulations for experiential learning in management education courses can provide a number of benefits that help students better understand and apply the concepts they are learning, while also developing valuable workplace skills such as problem-solving, communications and teamwork.…”
Section: Discussionsupporting
confidence: 61%
“…Tani et al (2021) found that BRT is a good model to predict student engagement and the reasons have a direct effect on engagement. Kulkarni et al (2022) state that self-determination theory (SDT) is a commonly used learning theory in gamification for disciplines such as education, psychology, neuroscience (Kulkarni et al , 2022), as well as human resource management (Gupta and Gomathi, 2017; Zimmerling et al , 2019). SDT focuses on factors that help to improve an individual’s (such as student learners) sense of autonomy, competence and their ability to relate to training programs.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…Gamification has also been examined using cognitive evaluation theory, behavior reinforcement theory, social comparison theory, rational choice theory, self efficacy theory, constructivist learning theory, and the technology-enhanced training effectiveness model. The most widely utilized theories are the self-determination theory, the low theory, and the goal-setting theory [8].…”
Section: Game-based Approachesmentioning
confidence: 99%
“…However, the normative charging of PA for all students' children and young has been critically discussed in sport pedagogy (Sortwell et al, 2022;Syrmpas et al, 2017). In this sense, gamification strategies seems to emerge, according to independent factors, such as age, sex and applications contexts (e.g., PE and/or sports games) (Fulton, 2019;Kulkarni et al, 2022;Pozo et al, 2018;Quintas et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These strategies leverage the motivational aspects of games to promote active participation, increase student motivation, and foster a deeper understanding of the subject matter. More important, gamification strategies have demonstrated short-term benefits (motivation and engagement in PE classes) and the long-term benefits (lifelong maintenance of PA, exercise and sports concepts) for children and youth (Kulkarni et al, 2022). It is important to note that gamification strategies should be thoughtfully designed, aligning with the learning goals and objectives of the educational context (Fulton, 2019;Kulkarni et al, 2022).…”
Section: Introductionmentioning
confidence: 99%